2021
DOI: 10.1101/2021.04.13.439750
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Visualizing cancer-originated acetate uptake through MCT1 in reactive astrocytes demarcates tumor border and extends survival in glioblastoma patients

Abstract: Glioblastoma is a devastating brain tumor with dismal prognosis of only 15-month survival regardless of surgical resection with few alternatives. Here, we report a reactive astrogliosis-targeted neuroimaging technique using the fusion of 11C-acetate PET and MRI (AcePET) extended the overall survival of patients by 5.25 months compared to conventional MRI-guided surgery. Targeted biopsy of 11C-acetate uptake-increased regions showed the signs of reactive astrogliosis with cancer stem cells at the boundary of hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…Additionally, in vitro studies showed that astrocytes surrounding the GBM lesions undergo astrogliosis and form reactive astrocytes [80]. Reactive astrocytes promote tumourigenesis, migration, and invasion through producing connective tissue growth factor (CTGF) [80][81][82]. CTGF binds to integrin β1 and activates the NF-κB signalling pathway.…”
Section: Astrocytesmentioning
confidence: 99%
“…Additionally, in vitro studies showed that astrocytes surrounding the GBM lesions undergo astrogliosis and form reactive astrocytes [80]. Reactive astrocytes promote tumourigenesis, migration, and invasion through producing connective tissue growth factor (CTGF) [80][81][82]. CTGF binds to integrin β1 and activates the NF-κB signalling pathway.…”
Section: Astrocytesmentioning
confidence: 99%
“…[13][14][15] Previous studies have confirmed that 11 C-ACE uptake is attributable to reactive astrocytes via monocarboxylate transporter 1 at the tumor boundary. 16 As an imaging tracer for reactive astrogliosis, high C-ACE uptake has been significantly associated with high-grade gliomas and poor prognosis. 17,18 It is currently unclear whether reactive astrogliosis imaging has any advantages over conventional imaging for tumor classification and survival prediction in patients with cerebral gliomas.…”
mentioning
confidence: 99%
“…In contrast to tumor-directed amino acid radiotracers, 11 C-acetate (ACE) targets reactive astrogliosis in the tumor microenvironment (TME) and has been associated with reactive astrocytes under inflammatory conditions in the CNS 13–15 . Previous studies have confirmed that 11 C-ACE uptake is attributable to reactive astrocytes via monocarboxylate transporter 1 at the tumor boundary 16 . As an imaging tracer for reactive astrogliosis, high 11 C-ACE uptake has been significantly associated with high-grade gliomas and poor prognosis 17,18 …”
mentioning
confidence: 99%